Digitalising mental health care: Practical recommendations from the European Psychiatric Association - Janos L. Kalman; Gerrit Burkhardt; Jerzy Samochowiec; Christian Gebhard; Geert Dom; Miriam John; Ozge Kilic; Tamas Kurimay; Lars Lien; Meryam Schouler-Ocak; Diego Palao Vidal; Jan Wiser; et al. (European Psychiatry, 2024)
The digitalisation of mental health care is expected to improve the accessibility and quality of specialised treatment services and introduce innovative methods to study, assess, and monitor mental health disorders. In this narrative review and practical recommendation of the European Psychiatric Association (EPA), we aim to help healthcare providers and policymakers to navigate this rapidly evolving field. We provide an overview of the current scientific and implementation status across two major domains of digitalisation: i) digital mental health interventions and ii) digital phenotyping, discuss the potential of each domain to improve the accessibility and outcomes of mental health services, and highlight current challenges faced by researchers, clinicians, and service users. Furthermore, we make several recommendations meant to foster the widespread adoption of evidence-based digital solutions for mental health care in the member states of the EPA. To realise the vision of a digitalised, patient-centred, and data-driven mental health ecosystem, a number of implementation challenges must be considered and addressed, spanning from human, technical, ethical–legal, and economic barriers. The list of priority areas and action points our expert panel has identified could serve as a playbook for this process.